DEVELOPING ENGLISH READING MATERIALS BY USING SCIENTIFIC APPROACH FOR THE GRADE X STUDENTS OF COMPUTER ENGINEERING AND NETWORKING PROGRAM AT SMKS TAMAN SISWA MEDAN - Hotmian Sitorus; Dr. Anni Holila Pulungan, M.Hum.; Nora Ronita Dewi, S.Pd., S.S., M.Hum. (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
This study concerns on how reading text are developed for vocational school. This study was conducted by using Research and Development (R&D) design. It was started from collecting the data, analyzing data, designing course grid, designing new reading material by using Scientific Approach, validating by experts, and revising for final product. The new reading material contained of five stages namely; observing, questioning, exploring, associating, and communicating. The source of data of this study was the grade X students of Computer Engineering and Networking Program at SMKS Taman Siswa Medan consisting 24 students. Instrument of collecting data were observation, questionnaire, and interview. After analyzing data, the researcher got the students‟ need in learning English in term of vocation that they have. The interview and questionnaire result proved that the students need English reading materials which contain English for Computer Engineering and Networking program. The materials which were developed were focused on descriptive text. The product had been validated by the experts. The average scores are 3,4 both from English teacher and English lecturer. It means the developing materials categorized as relevant for students of Computer Engineering and Networking program grade X.